Burnout in Chinese coal mine safety supervision. (October 2015) - Chen, Hong; Chen, Feiyu; Zhu, Dandan; Qi, Hui; Long, Ruyin
Abstract: This study examines commonly-suffered job burnout as it relates to the practice of safety supervision in Chinese coal mine enterprises. Commonly-suffered job burnout is a form of job burnout caused by external factors. It is closely related to task characteristics rather than individual idiosyncrasies. To explore the causes of commonly-suffered job burnout, the special attributes (the integrated output attributes, conditional output attributes, and public goods attributes) of coal mine safety output and the inevitability of the invalidation of the bounded authority in safety supervision were analyzed in this study, which reveals the formation mechanism of commonly-suffered job burnout. Moreover, a confirmatory game model was constructed to analyze how the attributes of the safety output and bounded authority of safety supervision act on the safety output. The theoretical connotation of commonly-suffered job burnout was explained based on the job demands-resources theory. A comparative analysis of commonly-suffered job burnout and the job burnout that occurs in the traditional research object was also undertaken from the viewpoint of the job demands, which are determined by the characteristics of the work task and their corresponding coping resources. Policy suggestions were given based on interventions in commonly-suffered job burnout. Highlights: We discuss commonly-suffered job burnout in Chinese coal enterprises. We analyze the special attributes of coal mine safety output. We explore two main causes of commonly-suffered job burnout. We construct a game model to validate how the two causes act on safety output. We put forward related policy suggestions.